Analysis of grain yield in ten Iranian wheat cultivars grown under semi-arid conditions - Doghozlou, Maryam Jahani; Emam, Yahya (Journal of Cereal Research, 2022)
Increased wheat yields are an urgent priority for global food security. Phenological performance in relation to yield of tenmodern wheat varieties including Bayat, Azadi, Falat, Navid, Chamran, Marvdasht, Pishtaz, Shiraz, Sirvan and Baharan, which were released during the last five decades wasevaluated at Shiraz University, Shiraz, Iran. The superior cultivars in terms of grain yield (Sirvan, Baharan and Chamran), had also higher grains/m2 as well as higherbiological yield. Sirvan and Baharan also showed greater harvest indices (43.38% and 41.77% respectively). Booting stage was longer in cultivars with lower grain number (Navid, Bayat and Shiraz). The high yielding cultivars, (Sirvan, Baharan and Chamran)entered the stem elongation phase (SEP) earlier than others. It wasconcluded thatlonger duration of SEPwithout change in the anthesis timecan increase grain yieldin semi-arid regions